Analisis Pengaruh Budaya 5R dan Kinerja Karyawan Terhadap Kepuasan Pelanggan PT.Indoporlen - Mei Krismahariyanto; Mohamad Prastya (Jurnal Jaring SainTek, 2019)
The research using amount 100 of data which taken in proportionate stratified random sampling, the examination of data using in quantitative statistical with aid of correlation technique of SPSS method version 16.0, The Quantitative calculation through statistical analysis produces the result value of R coefficient 0,750 which contributes to the meaning both variables of 5S customs (X1) and employee performances (X2) have strong correlation against customer satisfaction (Y), valuable contribution / effect of both independent variables which observed to dependent variable (Y) was expressed to R square value or coefficient determination R square (R2) result shown 0,892 or 89,2%. This value expressed that contribution / effect from both independent variables is 89,2% whereas the remain 1,8% was influenced by or revealed by another variables which loose observed. The result of F test taken from Anova as known that F count 5,112 is bigger than F table 3,0902 (5,112 > 3,0902) in significant a 0,05. The comparison value means both variables in mutual have any correlation to customer’s satisfaction